Cluster advantages in the state management of the financial resources of the agricultural sector in the Sakha (Yakutia) Republic - T. S. Rotar (Статистика и экономика, 2017)
The article is dedicated to the research of possibilities to use multivariate statistical analysis – cluster analysis – in developing measures for state management of the financial resources of agricultural sector in the Sakha (Yakutia) Republic.The research is based on the statistics methodology, theory of economics, and on the regional economics of the Sakha (Yakutia) Republic. Table methods of qualitative data visualization and statistical methods of social and economic phenomena and processes were used as a range of statistical tools in the research. Particularly, the method of cluster analysis was realized by the means of STATISTICA 10.0 application software package for the research purposes. It is known, that using the methodology of cluster analysis allows breaking the analyzed population into groups according similar indicators. For the research purpose, we managed to define the set of indexes, comprising the array of indicators, characterizing the development of agriculture in the region under research.It is noted that district clusterization in the analyzed Republic according to the indexes of agriculture development will enable to design the measures for financial resources management per each group of uluses of the region more effectively. This is the novelty of the research.It is noted that the obtained types are homogenous for their structure and meaningfully interpretable: Cluster 1 – districts with high level of agricultural production; Cluster 2 – districts with high financial indexes in agriculture; Cluster 3 – districts with low indexes of agriculture; Cluster 4 – the northern high-profitable districts; Cluster 5 – the northern districts with low indexes of agriculture; Cluster 6 – Yakutsk city, the capital of the Sakha (Yakutia) Republic.The main conclusion of the research is recommendation of the priority measures for agricultural financial resources management in the agricultural sector of the Sakha (Yakutia) Republic in order to arrange the conditions for sustainable financial support and social development of the regional agriculture. The research revealed that in the districts of the first cluster with high indexes of the main food resources production, management of the region should focus on the implementation of improvement programs for dairy and meat products processing and storage. Therefore, it is recommended to develop innovative investment activity to boost the level of technological infrastructure, needed for the mentioned measures. It is also emphasized, that the uluses (districts) of the second cluster need to specialize in manufacturing of crop and livestock farming products especially of industrial poultry production, which will eventually promote reasonable financial resources management. The management of the third cluster districts should review their financial expenses for the agricultural sector maintenance taking into account that each district has a great potential for the development of agriculture. In the districts of the fourth group, it is recommended to focus on the development of reindeer herders’ bases, as they receive the most tangible government support among the other northern districts, allow to develop reindeer breeding industry, therefore, to increase the indicator of their own financial resources as the main factor of finance management.The districts of the fifth cluster are considered to be abnormal because of low level of agriculture development, by virtue whereof it is recommended to resolve problems of population employment, execution of investment projects; it is also recommended to focus on reindeer and horse breeding industry. The sixth cluster is represented by the region capital, where currently the government program for devoting grants on the agriculture development, which will become a primary factor for maximizing the financial resources of the sector under study.